What's behind Macau's business disaster? - Morrison, Keith (Macau Business, 2022)
Macau, Macau Business, MAG, MB, MB Featured, Opinion | Business 101. When companies plan their business models, typically they must consider, amongst other matters: their products and/or services; demand; market(s) and their environments (economic, political, cultural, social); existing, potential, and likely competition; start-up and ongoing costs and expenses; emergency funding; marketing and promotion; income streams, revenue, and delayed profit; sales; distribution; cash flow; profit margins, gross and net; liabilities; risk analysis, evaluation, and handling; constraints and the ‘what if’ factor; flexibility, adaptability, and adjustment.
Section: Macau Business